Investigations of Artemisia Annua and Artemisia Sieberi Water Extracts Inhibitory Effects on β-Hematin Formation - Akkawi, Mutaz; Jaber, Suhair; Abu-Remeleh, Qassem; Lutgen, Pierre; Engeu Ogwang, Patrick (Med Aromat Plants, 2014)
Malaria is the most prevalent infectious disease in the world, killing 1-2 million people each year. New drugs are urgently needed to treat drug-resistant strains of malaria. In a previous study we found that extracts from Salvia palestinia leaves inhibited the formation of β-hematin with efficiency similar to that of chloroquine. The objective of this study was to investigate the effect of other plant extracts on hemozoin formation. A comparison between the efficiency of aqueous extracts or infusions of Artemisia annua from Luxembourg and Artemisia sieberi from Palestine in inhibiting β-hematin formation was done. Although it was found that the Artemisia sieberi leaf tea infusion was less effective than that of the Artemisia annua, the stem infusion of Artemisia sieberi was found to be better than that of Artemisia annua stems. Results obtained with infusions prepared with tap or well water may be different from results obtained in the laboratory with distilled water. Artemisia annua leaf infusions prepared using salt water (0.5g salt/150ml water) had higher efficiency in inhibiting β-hematin formation than those infusions done with distilled water. Mixing equal amounts of Artemisia annua leaf and Artemisia sieberi stem water extract showed an increase in their inhibitory effect on β-hematin formation. An important finding in this investigation was that the Artemisia annua lyophilized extracts lost activity with time, which may have an impact not only on in vitro laboratory results but also on in vivo treatment efficiency obtained with old extracts. In light of this finding it might be advisable to use Artemisia annua in the form of dried leaf powder and not in the form of extracts or infusion. Stored in dry, ventilated conditions the plant keeps its properties for many years.
Keywords: Artemisiaannua; Artemisia sieberi; Chloroquine; Hemozoin